Changes in Soil Chemical Properties of Gold Mine Tailings Land by Applying Oil Palm Empty Bunch Biochar and Rubber Litter Compost - Firnia, Dewi; Rohmayati, Imas; Hasyim, Abduh; Harfiah, Nida (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Pollution (Hg) of the soil due to gold mining activities reduces soil fertility and endangers the environment. The purpose of this study was to analyze effectiveness of biochar from palm empty bunches (PEB) and compost from rubber leaf litter as remedial materials to improve the soil chemical properties of Hg-contaminated tailings. An experimental method using a factorial Randomized Group Design was applied with varying doses of biochar and compost. Parameters observed included Hg concentration, pH, Organic C, Total N, and P and K availability. The results showed that the gold mine tailings have chemical properties that are not ideal for supporting plant growth, including a slightly alkaline pH, very low Organic C and total nitrogen contents, and mercury levels that exceed safe limits (The critical concentration of mercury (Hg) in soil is 0.3-0.5 ppm). The use of biochar from oil palm empty fruit bunches and rubber leaf litter compost proved to be able to increase pH, Organic C, total nitrogen, phosphorus, and available potassium. The treatment with the highest dose combination (30 tons PEB biochar and 20 tons rubber litter compost per ha) succeeded in increasing total N to 5.40%, available P by 175.67 mg/1kg, available K by 7.39 mg/100g, and Organic C by 0.98%. However, the amount of mercury remained high, so further remediation using larger doses of ameliorants and stricter tailings management is needed to sustainably reduce heavy metal pollution.